Bahtsul Masail sebagai Mazhab Fikih NU: Sebuah Perspektif - Adib, Muhammad; Syamsul A'dlom (MAQASHID, 2018)
This paper talks about the system of fiqh schools in Bahtsul Masail, especially in the context of the institution-based trend of fiqh schools in the modern era. Based on historical, normative, and sociological perspectives, this paper concludes that Bahtsul Masail has created a distinctive and unique system of fiqh schools, so that it has strong arguments to be called â€œthe NU fiqh schoolâ€